1982
DOI: 10.1042/bj2080413
|View full text |Cite
|
Sign up to set email alerts
|

Studies in vitro on shuttle systems of mouse spermatozoa

Abstract: Observations on systems reconstituted in vitro with different starting substrates (2-hydroxy-acids, 2-oxo-acids or leucine) indicate that a branched-chain 2-hydroxy-acid/2-oxo-acid shuttle for the transfer of reducing equivalents from cytosol to mitochondria may be operational in mouse sperm. Evidence is presented suggesting that the 2-oxo-acids produced by intramitochondrial oxidation of 2-hydroxy-acids ingressed from the cytosol can recycle back into the external phase. Observations in vitro demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
(9 reference statements)
4
22
0
Order By: Relevance
“…Effect of a-bromohydrin phosphate on the concentration of (a) dihydroxyacetone phosphate (DHAP) (n = 8) and (b) fructose-1,6-bisphosphate (F-l,6-P2) ( Cooney, 1987, Cooney andJones, 1988), or 3-bromopyruvate, which inhibits glyceraldehyde 3-phosphate dehydrogenase and 3-phosphoglycerate kinase , also prevented the production of C02, resulted in an increase in concen¬ trations of dihydroxyacetone phosphate and fructose-1,6-bisphosphate, but had no appreciable effect on the (Voet and Voet, 1995); the former is located in the cytoplasm whereas the latter is bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970 These results confirm those of Ford (1981) that, in boar spermatozoa, glycerol 3-phosphate is oxidized primarily by an FAD-dependent dehydrogenase that is probably extrinsically bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970). In this respect, boar spermatozoa are similar to those of rams (Ford, 1981), rats (Ford, 1981;Brooks, 1978;Schenkman et al, 1965) and cocks (Yamada and Terada, 1974) but not those of mice (Burgos et al, 1982) or humans (Ford, 1981). The ability of a-bromohydrin phosphate to inhibit this enzyme in boar spermatozoa is probably due to the R-isomer which has identical stereochemistry to the normal substrate (S)-(or sn·) glycerol 3-phosphate.…”
Section: Introductionsupporting
confidence: 77%
“…Effect of a-bromohydrin phosphate on the concentration of (a) dihydroxyacetone phosphate (DHAP) (n = 8) and (b) fructose-1,6-bisphosphate (F-l,6-P2) ( Cooney, 1987, Cooney andJones, 1988), or 3-bromopyruvate, which inhibits glyceraldehyde 3-phosphate dehydrogenase and 3-phosphoglycerate kinase , also prevented the production of C02, resulted in an increase in concen¬ trations of dihydroxyacetone phosphate and fructose-1,6-bisphosphate, but had no appreciable effect on the (Voet and Voet, 1995); the former is located in the cytoplasm whereas the latter is bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970 These results confirm those of Ford (1981) that, in boar spermatozoa, glycerol 3-phosphate is oxidized primarily by an FAD-dependent dehydrogenase that is probably extrinsically bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970). In this respect, boar spermatozoa are similar to those of rams (Ford, 1981), rats (Ford, 1981;Brooks, 1978;Schenkman et al, 1965) and cocks (Yamada and Terada, 1974) but not those of mice (Burgos et al, 1982) or humans (Ford, 1981). The ability of a-bromohydrin phosphate to inhibit this enzyme in boar spermatozoa is probably due to the R-isomer which has identical stereochemistry to the normal substrate (S)-(or sn·) glycerol 3-phosphate.…”
Section: Introductionsupporting
confidence: 77%
“…Although later studies from this and other laboratories [14][15][16][17][18][19][20][21][22][23] added more data supporting the cytosolic and intramitochondrial distribution of LDH C 4 , most of the evidence gathered was based on indirect methods of detection. Confirmation by direct techniques was still lacking.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in vitro have demonstrated that the shuttle functions by using the lactate/pyruvate redox couple [18] in some species, while in mouse STM it utilizes branchedchain 2-hydroxyacid/2-oxoacid pairs [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Correspondence: Kazuhiko Nishimura, 637-1, Hieda-cho, Yamatokohriyama-si, Nara, 639-11 Japan. drial respiratory chain is important in the production of energy [15,16]. Cytosolic NADH cannot traverse the mitochondrial membranes, so the reducing equivalents of cytosolic NADH are transferred to the mitochondria by shuttle systems.…”
Section: Introductionmentioning
confidence: 99%